Do hospital admission rates increase in colder winters? A decadal analysis from an eastern county in England. (5th July 2017) - Patterson, Stephen
Abstract: Background: The aim of the study was to measure the effect of colder winters compared to warmer winters on hospital admission rates in Suffolk County. Methods: The setting of this study was Suffolk County in eastern England. The period of the study was financial years 2003/04–2012/13. The study was an analytic ecological study. Analysis involved calculation of rate ratios of hospital admission rates in colder winters compared to warmer winters, in all persons and the elderly. Results: The main finding of the study was that all rate ratios for hospital admission rates in colder winters compared to warmer winters were significantly raised with effects of 2–5%. Rate ratios for all admissions in persons of all ages and persons aged 65 years and over were, respectively, 1.02 (99% confidence interval (CI): 1.01, 1.03; P < 0.001) and 1.02 (99% CI: 1.01, 1.04; P < 0.001). Rate ratios for emergency admissions in persons of all ages and persons aged 65 years and over were, respectively, 1.05 (99% CI: 1.03, 1.06; P < 0.001) and 1.04 (99% CI: 1.01, 1.06; P < 0.001). Conclusion: In Suffolk County, hospital admission rates are significantly raised in colder winters compared to warmer winters. This evidence may be useful in planning hospital services.